PERSPECTIVES ON JOB HAPPINESS AND HARMONY AMONG HUMAN CAPITAL: EVIDENCE FROM DUBAI - Opulencia, Maria Jade Catalan-; Fadahunsi, Akinola; Ali, Mouza Al (International Journal of Psychosocial Rehabilitation, 2020)
Philosophers and social researchers have described happiness in different ways (Kesebir & Diener, 2008). In evaluation to the hedonic view of happiness as concerning best emotions and judgments of pride, eudemonic nicely-being, self-validation, self-actualization, and associated principles propose that a happy or “correct” life entails doing what is right and virtuous, growing, pursing vital or self-concordant desires, and the usage of and developing one’s abilities and capabilities(Ryan and Deci, 2001; Ryff & Singer, 2008). Productive employees can benefit the government which effect of optimism on the economy and growth when people have faith in the future (Shk. Mohammed, 2017). The study examined human capital (n=156) in Dubai so to determine the job happiness and harmony in the workings of job satisfaction at the workplace. Descriptive method was used utilizing a case study and survey questionnaire as well as in depth interviews for data gathering. The findings suggest very positive which helped organizations enhance its performance, career growth opportunities and job satisfaction which played essentials for competitive advantage in the marketplace. The organizations have worked out for initiatives on the culture of happiness among the talents in dealing with their clients, peers and superiors. However, it will be appropriate to recommend for the organizations to have an integrated approach of happiness program.